Disclosure Of Key Audit Matters Concerning Audit Quality And Audit Delay On The Indonesia Stock Exchange - Putu Wistika Tresnanda Gandhy; Bambang, Bambang (International Journal of Economics, Business and Innovation Research, 2024)
Abstract This study aims to examine the effect of implementing Key Audit Matters (KAM) on audit quality and auditor independence in companies within the primary and non–primary sectors listed on the Indonesia Stock Exchange (IDX) throughout 2023. Purposive sampling was used to select samples, with 82 companies from the primary and non–primary sectors chosen as the research sample. Data analysis was conducted using the linear regression method, where audit quality was measured using the audit report lag and analyzed through descriptive statistical tests, model tests, and classical assumptions tests, such as normality and multicollinearity tests, with the assistance of Eviews 12 software. Meanwhile, audit delay was evaluated through various statistical tests, including multiple linear regression.